Market-Based and Accounting-Based Financial Reporting Quality and Investor Decision-Making: Evidence from Indonesian Manufacturing Firms - Abdul Nasser Hasibuan; Nik Mohd Azim Nik Ab Malik; Ahmad Afandi; Windari Windari (Jurnal Ilmiah Peuradeun, 2026)
The rapid growth of investors in emerging capital markets is not always accompanied by improvements in financial reporting quality, raising concerns about the role of financial information in investor decision-making. This study examined the influence of market-based and accounting-based financial reporting quality on investor decision-making in manufacturing firms listed on the Indonesia Stock Exchange. Using a quantitative explanatory design, the study analyzed panel data from 132 firms during 2018–2023, resulting in 792 firm-year observations. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings revealed that the quality of both market-based and accounting-based financial reporting positively and significantly influence investor decision-making. However, market-based quality exerted a greater impact, suggesting that investors relied more on information conveyed by market mechanisms than on internal accounting characteristics. The study contributes to the literature by demonstrating that financial reporting quality operates as a multidimensional construct with complementary, yet asymmetrical effects on investor behavior. The findings emphasize the importance of improving not only accounting quality but also the timeliness and market relevance of financial information in emerging capital markets.